Brand Equity, Customer Satisfaction & Loyalty: Malaysian Banking Sector - Hashim, Sharizal; Che-Ha, Norbani (2007)
Services cannot be seen, felt, tasted or touched in the same manner in which goods can be sensed. Therefore, the key to success in services marketing is to ‘tangibilizing the intangible’ by using an extrinsic cue like a brand. Moreover, brands that are high in brand equity are organization powerful assets. They can lead to customer satisfaction and customer loyalty. This study is to explore customer perceptions on brand equity dimensions among consumers of bank services in Malaysia. The results show brand meaning is an important factor to create brand equity that will lead to customer satisfaction and loyalty.